2018
DOI: 10.1007/s00604-018-2730-9
|View full text |Cite
|
Sign up to set email alerts
|

A paper-based competitive lateral flow immunoassay for multi β-agonist residues by using a single monoclonal antibody labelled with red fluorescent nanoparticles

Abstract: An ultrasensitive paper based lateral flow assay is described for rapid and simultaneous fluorometric detection of several β-agonists including clenbuterol and its chemical analogues (mabuterol, brombuterol, cimaterol, cimbuterol, bromchlorbuterol and banbuterol). A nonspecific monoclonal antibody (mAb) against clenbuterol and its analogues was prepared and employed in a competitive immunoassay where mAb conjugated to fluorescent nanoparticles and free β-agonists compete for the binding sites. This enables rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…A wax-based technology was applied to modify hydrophobic patterns and hydrophobic barriers on paper using a wax printer [27] and a pen-writing approach [28]. Different nanomaterials, such as quantum dots (QDs) [29][30][31][32][33], gold nanoparticles (AuNPs) [24,[34][35][36][37][38][39][40][41][42][43][44][45][46], AuNFs MBA @Ag [47] Cu-Pd/rGO nanoparticles [48], upconverting fluorescent nanocrystals [49], metal-organic framework [50], fluorescent nanoparticles [51], gold nanocage [52], gold nanorods [53], multi-walled carbon nanotubes and graphene oxide [54] and polymer nanoparticles [55], have also been used as reading signal in paper-based POCT devices. The functional papers prepared by these advanced modification approaches significantly extend the application potential of paper as the substrate of POCT devices.…”
Section: Introductionmentioning
confidence: 99%
“…A wax-based technology was applied to modify hydrophobic patterns and hydrophobic barriers on paper using a wax printer [27] and a pen-writing approach [28]. Different nanomaterials, such as quantum dots (QDs) [29][30][31][32][33], gold nanoparticles (AuNPs) [24,[34][35][36][37][38][39][40][41][42][43][44][45][46], AuNFs MBA @Ag [47] Cu-Pd/rGO nanoparticles [48], upconverting fluorescent nanocrystals [49], metal-organic framework [50], fluorescent nanoparticles [51], gold nanocage [52], gold nanorods [53], multi-walled carbon nanotubes and graphene oxide [54] and polymer nanoparticles [55], have also been used as reading signal in paper-based POCT devices. The functional papers prepared by these advanced modification approaches significantly extend the application potential of paper as the substrate of POCT devices.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the sensitivity of LFIA, other labels such as fluorescent nanoparticles have been employed in LFIA fabrication. An ultrasensitive fluorescent LFIA has been prepared with a nonspecific monoclonal antibody [35]. This fluorescent LFIA can rapidly screen for seven β-agonists within 8 min with an LOD lower than 50 pg/g of pork.…”
Section: Preparation and Application Of Generic Antibodiesmentioning
confidence: 99%
“…In one sense, broad-specific recognition elements have been developed with the aim of detecting several compounds in a group or a class. As a matter of fact, class-selective antibodies have been prepared and used to measure several analytes (within a class of compounds) by means of LF devices [27][28][29]: Zhang et al developed a monoclonal antibody, which was able to recognize three major ochratoxins, and based on this mAb, they proposed a LFIA for the simultaneous detection of the three hazardous substances. [27].…”
Section: Multiplexing Lfia Based On the Probementioning
confidence: 99%
“…Similarly, Xie et al generated a monocolonal antibody that equally recognizes avermectin and ivermectin and employed it for setting up a dual LFIA [28]. Notably, Wang R. et al reported a xLFIA for measuring up to 7 β-agonists in a single run by using a monoclonal that recognized clenbuterol and its analogues [29].…”
Section: Multiplexing Lfia Based On the Probementioning
confidence: 99%